2023
DOI: 10.1007/s10439-023-03314-x
|View full text |Cite
|
Sign up to set email alerts
|

AI-ChatGPT/GPT-4: An Booster for the Development of Physical Medicine and Rehabilitation in the New Era!

Abstract: Artificial intelligence (AI) has been driving the continuous development of the Physical Medicine and Rehabilitation (PM&R) fields. The latest release of ChatGPT/GPT-4 has shown us that AI can potentially transform the healthcare industry. In this study, we propose various ways in which ChatGPT/GPT-4 can display its talents in the field of PM&R in future. ChatGPT/GPT-4 is an essential tool for Physiatrists in the new era.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In general, it must also be noted that, so far, most research has only been applied to a selection of people willing to take part in testing this kind of innovative rehabilitation interventions. It was also found that their implementation may be hampered by legal and financial barriers [ 37 , 38 , 39 , 40 , 41 ].…”
Section: Models Of Rehabilitation For People With Inflammatory Arthritismentioning
confidence: 99%
“…In general, it must also be noted that, so far, most research has only been applied to a selection of people willing to take part in testing this kind of innovative rehabilitation interventions. It was also found that their implementation may be hampered by legal and financial barriers [ 37 , 38 , 39 , 40 , 41 ].…”
Section: Models Of Rehabilitation For People With Inflammatory Arthritismentioning
confidence: 99%
“…With the advent of ChatGPT, several steps underlying the decision-making processes could be supported. Indeed, ChatGPT’s capabilities can be harnessed in neurorehabilitation to assist with tasks such as planning agendas, booking appointments, and managing medication schedules for individuals recovering from brain injuries or strokes ( Peng et al, 2024 ). Its linguistic abilities can facilitate conversation, which is particularly beneficial for patients with speech or language deficits.…”
Section: Future Directionsmentioning
confidence: 99%
“…Education is an important part of rehabilitation. By interacting with ChatGPT, the patients and their families can be educated about the importance, goals, and benefits of rehabilitation 12 . Another major benefit of using ChatGPT in PMR is speeding up administrative work as it can generate documents that are necessary for routine practice such as letters of medical necessity for special medications in movement disorders clinics.…”
Section: Clinical Settingsmentioning
confidence: 99%